Probiotic effects (Bacillus cereus and Bacillus subtilis) on growth and physiological parameters of silver catfish (Rhamdia quelen) - Lins Rodigues, Mariana; Damasceno, Danielle Zanerato; Gomes, Ricárcio Luan Marques [UNESP]; Sosa, Bruno dos Santos [UNESP]; Moro, Evandro Bilha [UNESP]; Boscolo, Wilson Rogério; Bittencourt, Fábio; Signor, Altevir (Wiley, 2021)
This study aimed at evaluating the effects of a probiotic additive in productive performance and physiological parameters for Rhamdia quelen. The fish were fed diets containing increasing levels of the additive (0.15; 0.30; 0.45; and 0.60 g/kg of feed), which consisted of a blend of Bacillus cereus and B. subtilis, both at the concentration of 4 × 1011 CFU). Productive performance parameters were higher in fish fed diets containing 0.60 g/kg of the probiotics. Both the proximate composition and carcass yield were affected when 0.30 and 0.60 g/kg of the additive was included, whilst serum biochemical parameters were higher in fish fed diets containing 0.60 g/kg of the additive. An increase in the hepatic oxidative stress activity was found when 0.30 g/kg was supplied. The development of intestinal villi was influenced by the inclusion of the additives, as well as the activity of mucous-secreting cells in the tissue. Hepatocyte's growth was differential in fish fed diets containing 0.30 g/kg and other tissue alterations were found using 0.60 g/kg of the additive. The inclusion of 0.60 g/kg of the probiotic in diets for R. quelen enhances its growth performance and physiological status.
Keywords: biotechnology; fish farming; immunomodulatory; native species; non-pathogenic bacteria